Better Judgement-2 : Improving Assessors' Management of Factors Affecting their Judgement : Final Report. - Schmidt, Lisa; Schuwirth, Lambert; O'Keefe, Maree; King, Svetlana (Office for Learning and Teaching, 2016)
Better Judgement will improve assessors' expertise in oral and practice-based assessment by producing a complete assessor training programme and a set of training guides. A particular challenge in these assessment settings is their face-to-face nature which may lead to judgement biases. Judgement biases in assessment are not prejudices, instead they are incorrect representations in the assessor's mind of what has occurred during the assessment. Biases are natural and cannot be stopped from occurring but we can train assessors to recognise, name and manage them. The Better Judgement project designed, implemented and disseminated a training programme for assessors on how to recognise, prevent and counteract the influence of judgement biases on the assessment process. It was targeted at those assessors who are involved in oral and practice-based assessment so the project outcomes will contribute to the validity of assessing students in practice settings.